Tepung okra (Albelmoschus esculantus) menurunkan rasio kadar LDL terhadap HDL tikus hiperkolesterolemia - Ayu Febriyatna; Agatha Widiyawati (Alma Ata University Press, 2017)
ABSTRACTBackgounds: Hypercholesterolemia is one cause of heart disease with high levels of Low Density Lipoprotein (LDL) cholesterol and low levels of high density lipoprotein (HDL) cholesterol. Okra (Albelmoschus esculantus) flour contain high fibers and more bioactive compound such as flavonoids. Objectives: This study aimed to examine the effectiveness of okra flour against the Low Density Lipoprotein (LDL) cholesterol level and high density lipoprotein (HDL) cholesterol level in Hypercholesterolemic rats. Methods: Design of the study was experimental design with pre-and posttest control goup. Male white rats (rattus norvegicus) aged 8-10 weeks with body weight of 150-200 g were used, then divided into 4 goups of 8 rats. Rats made Hypercholesterolemia used Haight Fat Diet (HFD) feed at a doses 4mg/100 g body weight for 14 days. After that, Hypercholesterolemic rats were provided by standard diet rats given standart feed and okra flour with different doses it was goups positive control (KP) not given flour okra, okra flour doses 0.09 g/200 g bofy weight (P1), okra flour doses 0.18 g/200 g body weight (P2), and okra flour doses 0.36 g/200 g body weight (P3). The data was analyzed using One Way ANOVA dan paired t-test.Results: Rats in all goup did not experience changes in body weight significantly. Concentration of HDL cholesterol increased significantly in P3 goups with doses okra flour 0.36 g/200 g body weight compared withe the other goups. P3 goups attenuated the concentration of LDL cholesterol. Conclusions: the administration okra flour (albelmoschus esculantus) at doses 0.36 g/200 g body weight improved HDL cholesterol and decreased LDL cholesterol concentration in Hypercholesterolemic rats model . KEYWORDS: Hypercholesterolemic High Density Lipoprotein (HDL), Low Density Lipoprotein (LDL) and Okra Flour. ABSTRAK Latar belakang: Hiperkolesterolemia adalah salah satu penyebab penyakit jantung yang ditandai dengan kadar kolesterol Low Density Lipoprotein (LDL) yang tinggi dan kadar kolesterol High Density Lipoprotein (HDL) yang rendah. Okra (Albelmoschus esculantus) dalam bentuk tepung mengandung serat yang tinggi dan kandungan bioaktif seperti flavonoid. Tujuan: Penelitian ini untuk mengetahui efektifitas tepung okra terhadap perubahan kadar kolesterol HDL dan LDL pada tikus putih model hiperkolesterolemia. Metode: Desain penelitian ini yaitu true experimental dengan Kelompok Kontrol (Pretest-Posttest with Control Goup). Tikus putih jantan (Rattus novergicus) yang berumur 8-10 minggu dengan bobot antara 150-200 g dibagi kedalam 4 kelompok. Tikus dibuat hiperkolesterolemia menggunakan pakan HFD dengan dosis 4 mg/100 g BB tikus perhari selama 14 hari. Selanjutnya, tikus hiperkolesterolemia diberi pakan pakan standart dan tepung okra dengan dosis yang berbeda yaitu kelompok KP (Kontrol Positif) hanya diberi pakan standar, kelompok P1 (tepung okra dosis 0,09 g/200 g BB tikus perhari), kelompok P2 (tepung okra dosis 0.18 g/200 g BB tikus perhari), dan kelompok P3 (tepung okra dosis 0,36 g/200 g BB tikus perhari) selama 10 hari. Data dianalisis menggunakan One Way ANOVA dan paired t-test. Hasil: Tikus percobaan pada semua kelompok tidak terjadi perubahan berat badan yang signifikan. Kadar kolesterol HDL mengalami peningkatan yang signifikan pada kelompok P3 dengan dosis tepung okra 0.36 g/200 g dibandingkan dengan kelompok yang lainnya. Kelompok P3 juga mampu menurunkan kadar kolesterol LDL.Kesimpulan: tepung okra (albelmoschus esculantus) pada dosis 0.36 g/200 g BB tikus/hari selama 10 hari secara bermakna berpengaruh terhadap peningkatan kadar kolesterol HDL dan penurunan kadar kolesterol LDL tikus model hiperkolesterolemia KATA KUNCI: Hiperkolestrolemia, High Density Lipoprotein (HDL), Low Density Lipoprotein (LDL), tepung okra